Idea translation approach adapted by novice designers in furniture mean-making - Ali, Abu; Mohd Yusof, Wan Zaiyana; Isa, Siti Salwa; Liem, Andre; Isa, Siti Suriawati; Jamaludin, Nor Lelawati; Mohd Nasir, Junita Shariza (Springer, 2023)
This research aims to understand sources of inspiration, both in defining the context for new designs and in informing the creation of individual designs by 14 novice designers. The motivations for this study lie in the evidence that the quest for originality, cultural aspiration, intimacy with the object, as well as the practicality of furniture, are the significant factors that influence the purchase of furniture and the growth of this business. In this paper, we discuss the inspirational tools and techniques in form-giving adapted by novice designers and what information is used to convey their ideas. We see it as the application of a language to the area of potential design concept generation. In a study of furniture design, we have observed that novice designers communicate with each other about new designs, styles, and moods, largely by reference to the sources of analogy especially symbol analogy.